2019
DOI: 10.1111/bph.14600
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in mouse models of fear inhibition: Fear extinction, safety learning, and fear–safety discrimination

Abstract: Background and Purpose:Women are overrepresented in post-traumatic stress disorder (PTSD), a mental disorder characterised by ineffective inhibition of fear.The use of male animals dominates preclinical studies, which may contribute to a lack of understanding as to why this disparity exists. Thus, the current study explores sex differences in three mouse models of fear inhibition.Experimental Approach: All experiments tested male and female C57Bl/6J mice.Experiment 1 employed two fear conditioning protocols, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 44 publications
6
22
1
Order By: Relevance
“…In contrast to our results, other studies have found no sex differences in fear discrimination [42][43][44][45] . Another study found enhanced cued fear discrimination in females, compared to males, with one training session but no sex differences in fear discrimination or safety signalling with repeated training sessions 23 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, other studies have found no sex differences in fear discrimination [42][43][44][45] . Another study found enhanced cued fear discrimination in females, compared to males, with one training session but no sex differences in fear discrimination or safety signalling with repeated training sessions 23 .…”
Section: Discussioncontrasting
confidence: 99%
“…After extended auditory fear discrimination training, we recorded local field potentials (LFPs) in mPFC during retrieval testing to determine if discrimination and generalization in males and females, respectively, are characterized by sex differences in mPFC function. The prelimbic (PL) and infralimbic (IL) subregions of mPFC play opposing roles in the expression and extinction of learned fear 4 and we have previously shown sex differences in theta (4-12 Hz) and low gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) oscillations in these areas during learned fear expression and extinction 14,15 . As there is also evidence for distinct contributions of PL and IL to fear discrimination 29,36 , we recorded LFPs from both of these mPFC subregions at retrieval.…”
mentioning
confidence: 99%
“…Subsequent studies also found higher variability in the behaviour of female rats (see, e.g., Broadhurst, 1957). A recent study has extended these findings by studying processes involved in fear conditioning, which clearly differ in males and females, especially during extinction (Clark, Drummond, Hoyer, & Jacobson, 2019).…”
Section: Evidence For Sex Differences That Affect Pharmacologymentioning
confidence: 91%
“…The importance of generating gender-specific products of learning and memory research is underscored by more recent reports demonstrating a significant degree of sexual dimorphism in fear learning and memory, and related disorders. For example, despite men experiencing greater levels of exposure to trauma, the prevalence of PTSD in women is twice that of men, and women experience more severe symptoms (Merz et al 2018 ; Clark et al 2019 ; Inslicht et al 2013 ; Chen et al 2014 ; Farrell et al 2013 ). While this would suggest that sexual maturity and the associated variation in sex hormone signaling might play a role in these sexual dimorphisms, the literature is conflicting, and it is not clear whether hormonal fluctuations in the estrous cycle influence the prevalence and severity of PTSD in females (Cossio et al 2016 ; Zhao et al 2018 ; Kirry et al 2019 ; Graham and Scott 2018 ; Maeng et al 2017 ; Graham and Daher 2016 ; Kobayashi et al 2020 ; Maddox et al 2018 ; Day and Stevenson 2020 ; Day et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%